Unbound bilirubin predicts abnormal automated auditory brainstem response in a diverse newborn population - Ahlfors, CE (J Perinatol, 2009)
OBJECTIVE: The objective of this study was to determine if plasma unbound or ‘free’ bilirubin concentration (B(f)) measured during the first 30 days of life is associated with subsequent abnormal hearing screening testing by automated auditory brainstem response (AABR) in a diverse population of newborns. STUDY DESIGN: An observational study of newborns receiving AABR, plasma total bilirubin concentration (TBC) and B(f) measurements and without underlying conditions known to affect hearing was conducted. Logistic regression was used to determine associations between abnormal AABR and B(f) or TBC. The impacts of a variety of clinical factors on the regression model were also assessed. RESULT: A total of 191 patients with birth weights and gestations ranging from 406 to 4727 g and 24 to 42 weeks, respectively, were studied. Among them, 175 (92%) had normal (bilateral PASS) AABR and 16 had abnormal AABR (6 had unilateral REFER AABR, and 10 had bilateral REFER AABR). Mean TBC was not significantly different in babies with normal or abnormal AABR, but mean B(f) was greater in the latter group (1.76 versus 0.93 µg per 100 ml, respectively, P = 0.012). B(f), but not TBC, was associated with an abnormal AABR (B(f) adjusted odds ratio 3.3, 95% CI 1.8 to 6.1). Comparing receiver-operating characteristics curves, the B(f)/TBC ratio was a better predictor of an abnormal AABR than B(f) alone. Intraventricular hemorrhage was the only confounding clinical variable. CONCLUSION: An abnormal AABR is associated with an elevated B(f) or B(f)/TBC ratio, but not the TBC alone. The prevalence of bilirubin neurotoxicity as a cause of audiological dysfunction may be underestimated if the TBC alone is used to assess the severity of newborn jaundice.